Pengembangan Keterampilan Berpikir Kritis (HOTS) di SDIT Bina Insani Muslim: Studi Integrasi Kurikulum dan Praktik Pembelajaran - Elkarimah, Mia Fitriah (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2025)
This study aims to analyze the implementation of Higher Order Thinking Skills (HOTS) in the curriculum and learning strategies at SDIT Bina Insani Muslim Jatimulya, Bekasi. HOTS is crucial in the digital era as a response to the demands of 21st-century competencies, especially in the context of basic education based on the Qur'an which not only emphasizes memorization but also the ability to analyze, evaluate, and create innovative solutions based on Qur'anic values. This study uses a descriptive qualitative approach, with data obtained through direct observation for five months, supplemented by document analysis (SDIT Bina Insani Muslim Curriculum 2020-2025 and the Ministry of Religion's policy on HOTS-based PAI), as well as relevant literature studies. All data were analyzed based on the Revised Bloom's Taxonomy framework and the 4C Concept (Critical Thinking, Creativity, Collaboration, Communication). The results of the study indicate that SDIT Bina Insani Muslim has systematically integrated HOTS through an integrated curriculum that combines the 2013 Curriculum, JSIT, and local content. The focus on creative tahfizh, contextual learning, and collaborative projects effectively aims to shape students' analytical and evaluation skills, while developing their 4C skills. Active learning strategies such as Problem-Based Learning (PBL), multidisciplinary simulations, and Islamic values ​​debates, combined with spiritual activities (dhuha prayer and muraja'ah) integrated with storytelling and literacy, significantly support the development of HOTS. However, the implementation of HOTS still faces several significant challenges, namely the gap in teacher training related to HOTS, limited supporting facilities and infrastructure (computer laboratories, digital libraries, interactive teaching aids), and limited learning time due to tight schedules. This study recommends the need for increased teacher training and optimization of facilities to support HOTS learning more effectively at SDIT Bina Insani Muslim.